Siasatan kes jenayah syariah di bawah Akta Prosedur Jenayah Syariah (Wilayah-wilayah Persekutuan) 1997 - Ahmad ‘Azam Mohd Shariff,; Mazupi Abdul Rahman, (Fakulti Undang - Undang, 2005)

(untitled)
The Syariah Criminal Procedure (Federal Territories) Act 1997 is a Syariah Act which has been passed by the Parliament in 1997 and being enforced in the Federal Territory. Now, some eight years after its first implementation, this article attempts at analyzing the procedures of investigation in syariah criminal cases from the perspective of the syariah. This article, simultaneously, intends to look into the effectiveness of the general enforcement of the relevant legal provisions in the said Syariah Act while presenting some practical suggestions on improving their enforcement. Such practical suggestions are important in ensuring smoother implementation of the law relating to syariah criminal investigation in the Federal Territory towards upholding justice for all and preserving the holiness of Islam as the official of the country